Implementing enterprise risk management : from methods to applications - Lam, James (John Wiley & Sons, 2017)
Offering valuable insights on solving real-world business problems using enterprise risk management (ERM), this practical guide gives risk professionals a clear understanding of how to implement an enterprise risk management program for every business. - Resumé vydavatel Edited summary from book.
Obsahuje index.
Keywords: rizikový management; podnikatelská rizika; risk management; business risk; příručky; elektronické knihy; handbooks and manuals; electronic books